Mobile communication system for multimedia application - Kwong, Emily Wen Lin. (2011)
As technology advances, mobile phones are no longer like when they were just invented– to make phone calls. Mobile phones have incorporated much functionality for convenient reasons. This is where GPS comes into the picture, where A-GPS chips were installed in most mobile phones or smart phones nowadays; it provides consumers with the ability to locate them or for navigation purposes. However, GPS relies on a few crucial factors to operate, such as weather, availability of satellites and the environment. With drawbacks like such, it defeats the main purpose of locating and navigating indoors like shopping malls or buildings. Thus indoor positioning technique with Wi-Fi is essential to solve the drawbacks of GPS. With an application that allows both GPS service and Wi-Fi service, consumers are able to locate and navigate with just a smart phone. The application is developed with Android SDK and programmed in Java language. Android is an open platform for mobile development and provides framework to develop an application. The application is classified mainly into three categories, GPS service, Wi-Fi service and camera functionality. A main menu allows user to select which service to utilize upon start up. Camera functionality is inclusive of the automatic sending of SMS and uploading of the captured image to the web server, which then allows the user to download image that provides relevant information from web server. Experiments and analysis were done to achieve a higher accuracy to estimate indoor location of the mobile device. These include the method to obtain RSSI values, the placement of AP as well as the RSSI-distance relationship. The findings for RSSI- distance relationship have trends of exponential growth, which is corresponding to research by researchers and organizations.